Anion‐Responsive Tunable Bulk‐Phase Homochirality and Luminescence of a Cationic Framework. Issue 39 (21st August 2014) - Manna, Biplab; Joarder, Biplab; Desai, Aamod V.; Karmakar, Avishek; Ghosh, Sujit K.
Abstract Reaction of a linear bi‐chelating N‐donor achiral ligand with ZnII afforded a homochiral cationic framework with six‐fold one‐dimensional helical chains. The compound showed selective anion exchange behavior with interesting anion‐responsive tunable bulk‐phase homochirality. The cationic framework also presented anion‐driven variable luminescence and sorption behavior.